If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 3 * 12 + 11 Multiply 3 * 12 x = 36 + 11 Combine like terms: 36 + 11 = 47 x = 47 Solving x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Simplifying x = 47
| P=r(150-1.5r)-20(150-1.5r)-1500 | | =3*12+11 | | log(7)4n=0 | | 6.6x+8=4.6x+2 | | 9/4-3=9 | | -8x-9x=119 | | x-5/6-1=x-5/7 | | 19/5÷4 | | 8c+4.75=20 | | 11x+10-3x+(-7)=-9+2x | | 0.6x+14.1=x-7.3 | | 3x(4/2) | | 3(8x+9)-9x=7x+19 | | Y-0=1/4[x-(-4)] | | 14-2(3a+1)=2(3a-2) | | 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) |